2022
DOI: 10.3390/microorganisms10122496
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Feeding and Enzymatic Catabolism for Mannan-Oligosaccharide Utilization by the Butyrate-Producing Gut Bacterium Roseburia hominis A2-183

Abstract: β-Mannan is abundant in the human diet and in hemicellulose derived from softwood. Linear or galactose-substituted β-mannan-oligosaccharides (MOS/GMOSs) derived from β-mannan are considered emerging prebiotics that could stimulate health-associated gut microbiota. However, the underlying mechanisms are not yet resolved. Therefore, this study investigated the cross-feeding and metabolic interactions between Bifidobacterium adolescentis ATCC 15703, an acetate producer, and Roseburia hominis A2-183 DSMZ 16839, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…For example, the production of succinate by Bacteroidetes strains is intriguing for host homeostasis and inflammation regulation ( 34 ), while the production of GABA, an inhibitory neurotransmitter, could impact anxiety and depression disorders in mammals ( 35 ). In contrast, Firmicutes strains showed increased metabolite production in the presence of glucose and dietary carbohydrates, such as lactic acid ( 36 ). Interestingly, nicotinic acid production by S. variabile and E. rectale, irrespective of the culture condition, suggested a potential link to host nicotinamide adenine dinucleotide biosynthesis and a contribution to a symbiotic relationship in the gut microbiota ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the production of succinate by Bacteroidetes strains is intriguing for host homeostasis and inflammation regulation ( 34 ), while the production of GABA, an inhibitory neurotransmitter, could impact anxiety and depression disorders in mammals ( 35 ). In contrast, Firmicutes strains showed increased metabolite production in the presence of glucose and dietary carbohydrates, such as lactic acid ( 36 ). Interestingly, nicotinic acid production by S. variabile and E. rectale, irrespective of the culture condition, suggested a potential link to host nicotinamide adenine dinucleotide biosynthesis and a contribution to a symbiotic relationship in the gut microbiota ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-feeding mechanisms between bifidobacteria and potent butyrate-producing microorganisms have been reported by multiple researchers ( Rios-Covian et al, 2015 ; Moens et al, 2016 ; Rivière et al, 2016 ). Moens et al (2016) , for instance, reported specific cross-feeding interactions between different Bifidobacterium species and the butyrate-producing Faecalibacterium prausnitzii when providing the prebiotic inulin as a single nutrient source, while Bhattacharya et al (2022) observed metabolic interactions between Roseburia hominis and Bifidobacterium adolescentis upon dosing beta-mannan-oligosaccharides. Furthermore, the observed butyrogenic potential of EpiCor confirmed findings obtained in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the production of succinate by Bacteroidetes strains is intriguing for host homeostasis and inflammation regulation [34], while the production of GABA, an inhibitory neurotransmitter, could impact anxiety and depression disorders in mammals [35]. In contrast, Firmicutes strains showed increased metabolite production in the presence of glucose and dietary carbohydrates, such as lactic acid [36]. Interestingly, nicotinic acid production by S.…”
Section: Bacterial Responses To Dietary Carbohydrates Were Significan...mentioning
confidence: 99%